The Relationship between Anxiety Levels and Blood Sugar Levels in the Elderly - Ajeng Listianasari; Ning Arti Wulandari; Wimar Anugrah (Journal of Ners and Midwifery, 2023)
The increasing age, the more problems faced both physically and mentally such as loneliness, anxiety and depression. The prevalence of anxiety in the elderly is increasing. The increased release of the hormones cortisol and epinephrine in someone who is experiencing anxiety can affect an increase in gluconeogenesis and glycogenolysis which results in an increase in blood sugar levels. This study was to analyze the relationship between anxiety levels and blood sugar levels in the elderly. The research design uses a cross sectional approach. The sample for this research was 87 respondents who were taken by purposive sampling from 111 elderly people.Â  The results of the Pearson correlations test showed that there was a relationship between anxiety and blood sugar levels in the elderly with a p value = 0.000 (<0.05). Therefore, the elderly can control their anxiety to reduce the risk of increasing blood sugar levels which have an impact on the health of the elderly